The Fruits of Integration : Black Middle-Class Ideology and Culture, 1960-1990. - Banner-Haley, Charles T. (University Press of Mississippi, 2010)
In late twentieth-century America the black middle class has occupied a unique position. It greatly influenced the way African Americans were perceived and presented to the greater society, and it set roles and guidelines for the nation's black masses. Though historically a small group, it has attempted to be a model for inspiration and uplift. As a key force in the "Africanizing" of American culture, the black middle class has been both a shaper and a mirror during the past three decades. This study of that era shows that the fruits of integration have been at once sweet and bitter.